Antioxidant, anticholinesterase and tyrosinase inhibition activities, and fatty acids of Crocus mathewii - A forgotten endemic angiosperm of Turkey - EROL, EBRU; Yildiztekin, Fatma; Nadeem, Said; Erol, EBRU; Yildiztekin, Mahmut; Tuna, Atilla L.; Ozturk, Mehmet (My University, 2016)
Context We report the first ever chemical/biochemical study on Crocus mathewii Kerndorff (Iridaceae) - a Turkish endemic angiosperm. This plant has never been explored for its phytochemistry and bioactivities.Objective This study explores C. mathewii corm and aerial parts for the chemical and biological properties of hexane, ethyl acetate, methanol and water fractions of the extracts.Material and methods Plant material (20g) was extracted by methanol (250mLx5, 3 days each) and fractioned into hexane, ethyl acetate, methanol and water. All fractions were subjected to -carotene-linoleic acid, DPPH, ABTS(+), CUPRAC, metal chelating and tyrosinase inhibition activities. Hexane fractions were submitted to GC-MS analysis.Results Ethyl acetate fractions showed excellent IC50 values in DPPH (aerial 36.210.76 and corm 33.87 +/- 0.02mg/L) and ABTS(+) (aerial 33.01 +/- 0.79 and bulb 27.87 +/- 0.33mg/L); higher than the IC50 of the standard -tocopherol (DPPH 116.25 +/- 1.97; ABTS 52.64 +/- 0.37mg/L), higher than BHA in DPPH (57.31 +/- 0.25mg/L), but slightly lower in ABTS (19.86 +/- 2.73mg/L). Methanol extract of aerial parts also showed higher activity than -tocopherol in DPPH (85.56 +/- 11.51mg/L) but slightly less (72.90 +/- 3.66mg/L) than both the standards in ABTS. Linoleic (aerial 53.9%, corm 43.9%) and palmitic (aerial 22.2%, corm 18%) were found as the major fatty acids.Discussion and conclusion Some fractions of C. mathewii showed higher antioxidant activities than the standards. There is a need to explore more about this plant.